EFEKTIVITAS PERMAINAN NUMERASI SEBAGAI STRATEGI PEMBELAJARAN UNTUK MENINGKATKAN KESENANGAN SISWA - Jatmiko, Heru; Hidayat, Taufik; Priambodo, Anung (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2026)
Physical Education, Sports, and Health (PJOK) learning does not only focus on developing physical abilities but can also be integrated with the enhancement of students’ numeracy skills and affective aspects, such as learning enjoyment. However, monotonous PJOK instruction may reduce students’ enthusiasm for participating in learning activities. Therefore, innovative learning strategies are needed, one of which is the use of numeracy games in PJOK learning. This study aims to examine the effectiveness of numeracy games as a Project-Based Learning (PJBL)-based PJOK instructional strategy in increasing elementary school students’ learning enjoyment. This research employed an experimental method with a pretest–posttest control group design. The research subjects consisted of 50 students in the experimental group and students in the control group. The experimental group received PJOK instruction through PJBL-based numeracy games, while the control group was taught using conventional PJOK instruction. The results showed that the mean pretest score of learning enjoyment in the experimental group was 66.12, while the control group scored 66.45. After the intervention, the posttest mean score of learning enjoyment in the experimental group increased to 73.28, whereas the control group reached 68.14. The results of the t-test indicated a significance level of 0.002. Therefore, numeracy games in PJOK learning based on PJBL are effective in enhancing elementary school students’ learning enjoyment.